Performances of Plasma Sprayed Metal‐supported Solid Oxide Fuel Cell and Stack. Issue 6 (12th November 2018) - Tsai, C. H.; Hwang, C. S.; Chang, C. L.; Wu, S. H.; Lin, H. H.; Shiu, W. H.; Lin, J. K.; Yang, S. F.; Fu, C. Y.; Yang, C. S.
Abstract: The metal‐supported solid oxide fuel cell (MS‐SOFC) consisting of a porous Ni‐Mo as metal‐support, a La0.75 Sr0.25 Cr0.5 Mn0.5 O3– δ (LSCM) as diffusion barrier layer, a nano‐structured Ce0.55 La0.45 O3– δ (LDC)‐Ni as anode layer, a LDC as anode interlayer, a La0.8 Sr0.2 Ga0.8 Mg0.2 O3– δ (LSGM) as electrolyte, a Sm0.15 Ce0.85 O3– δ (SDC) as cathode interlayer, a 50 wt.% SDC–50 wt.% Sm0.5 Sr0.5 CoO3– δ (SSC) as composite cathode interlayer and a 25 wt.% SDC–75 wt.% SSC as cathode current collector are prepared by atmospheric plasma spraying (APS). The 25 cm 2 cell delivers maximum power densities of 962 and 1, 119 mW cm −2 at 700 and 750 °C. The durability, thermal cycling and redox cycling tests of this cell show the cell have good durability, thermal cycle stability and redox stability. The assembled single cell stack of 100 cm 2 cell shows electric output powers of 39 W (481 mW cm −2 ) and 27.4 W (338 mW cm −2 ) at 750 °C and 700 °C. The long‐term stability test of this single cell stack shows a degradation rate of about 0.77% k −1 h −1 over 1, 770 h at 400 mA cm −2 and 700 °C. Furthermore, a 25‐cell MS‐SOFC stack is assembled to evaluate the power performance and it shows a stack power of 829.8 W at 19.85 V and 740 °C.